Development Strategy of Halal Tourism Objects in Medan City - Silvia Handayani Siregar; Fauzi Arif Lubis; Nurul Jannah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the development strategy of halal tourism objects in Medan City. This study uses SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method to evaluate the internal and external factors that affect the development of halal tourism in this city. The analysis results show that Medan City has significant strengths, such as rich cultural potential, nature tourism, accommodation and ease of communication. However, there are weaknesses such as halal services that need to be improved, service quality, and less effective promotion. Significant opportunities were also identified, including the rapidly growing halal tourism market and the potential for increased international cooperation. However, threats such as competition from similar destinations, security issues, economic fluctuations, and related policy changes need to be addressed. The results of this study indicate the need for a targeted and sustainable development strategy to capitalize on the potential of halal tourism in Medan City. Therefore, the Medan City government undertakes a strategy that involves improving service quality, effective promotion, and stronger cooperation with stakeholders. This strategy is expected to develop Medan City as an attractive and sustainable halal tourism destination.